2019
DOI: 10.3390/jcm8081222
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Polyclonal-Derived CDR Peptides as an Innovative Strategy in Glaucoma Therapy

Abstract: The pathogenesis of glaucoma is strongly associated with the occurrence of autoimmune-mediated loss of retinal ganglion cells (RGCs) and additionally, recent evidence shows that specific antibody-derived signature peptides are significantly differentially expressed in sera of primary-open angle glaucoma patients (POAG) compared to healthy controls. Synthetically antibody-derived peptides can modulate various effector functions of the immune system and act as antimicrobial or antiviral molecules. In an ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 81 publications
1
20
0
Order By: Relevance
“…However, in a recent study of our group we identified the protein HTRA2 as a high-affinity interaction partner of the synthetic peptide ASGYTFTNYGLSWVR [ 16 ]. Thereby, this synthetic peptide encodes a complementary-determining region 1 (CDR1) of polyclonal antibody molecules, which was originally identified as a potential biomarker candidate in primary-open angle glaucoma (POAG) patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a recent study of our group we identified the protein HTRA2 as a high-affinity interaction partner of the synthetic peptide ASGYTFTNYGLSWVR [ 16 ]. Thereby, this synthetic peptide encodes a complementary-determining region 1 (CDR1) of polyclonal antibody molecules, which was originally identified as a potential biomarker candidate in primary-open angle glaucoma (POAG) patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, this synthetic peptide encodes a complementary-determining region 1 (CDR1) of polyclonal antibody molecules, which was originally identified as a potential biomarker candidate in primary-open angle glaucoma (POAG) patients [ 17 ]. Furthermore, the synthetic CDR1 peptide ASGYTFTNYGLSWVR induced neuroprotective effects on retinal ganglion cells (RGCs) in an organ culture model for glaucoma, and was also accompanied by specific proteomic changes in the CDR1-treated retinal explants [ 16 ]. These important findings lead to the assumption that HTRA2 might represent a key player in neurodegenerative diseases such as glaucoma, and may serve as a potential therapeutic target in the future.…”
Section: Introductionmentioning
confidence: 99%
“…11 Large-scale protein analyses are effectively performed with mass spectrometry-based proteomic techniques, which aim at identifying and quantifying the entire set of proteins in a given tissue or body fluid. [12][13][14][15][16] Proteome studies of aqueous humor may bring valuable insights into molecular changes following BRVO. 11,17 However, the human aqueous proteome of BRVO remains largely unstudied with mass spectrometry except for a study on aqueous humor from six BRVO patients, which was published by Yao et al 18 in 2013.…”
mentioning
confidence: 99%
“…With major advances in recent years, proteomic techniques allow for in-depth protein analysis that may elucidate molecular mechanisms underlying ocular diseases. [11][12][13][14][15][16][17] In…”
mentioning
confidence: 99%
“…In gel tryptic digestion was performed as described in detail previously and SOLAµ TM HRP Spin plates were used for peptide purification prior to LC-MS/ MS analysis with a Rheos Allegro Pump downscaling to a capillary HPLC system and coupled to a hybrid linear ion trap-Orbitrap MS system (LTQ Orbitrap XL; Thermo Fischer Scientific, Rockfeld, IL USA). Elution gradient of the HPLC and MS-specific parameters are described elsewhere in detail 38 . Parameters used for elution gradient and MS parameters were applied as described previously 39,40 .…”
Section: Proteomicsmentioning
confidence: 99%